2017
DOI: 10.1039/c6sc03184f
|View full text |Cite
|
Sign up to set email alerts
|

Exchange-bias quantum tunnelling in a CO2-based Dy4-single molecule magnet

Abstract: Herein the description of a CO2-based single molecule magnet, obtained through CO2 absorption in the presence of an organic base and a lanthanide is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 44 publications
3
23
0
Order By: Relevance
“…Substituting J Ising for J xx in our simulations (because x in the molecular frame is the most magnetic direction, Figure S25) does not yield avoided crossings consistent with the QTM steps observed in the hysteresis measurements (Figure S27) . Combining the dipole interaction matrix with the Ising approximation (i.e., Eqs.…”
Section: Figuresupporting
confidence: 64%
“…Substituting J Ising for J xx in our simulations (because x in the molecular frame is the most magnetic direction, Figure S25) does not yield avoided crossings consistent with the QTM steps observed in the hysteresis measurements (Figure S27) . Combining the dipole interaction matrix with the Ising approximation (i.e., Eqs.…”
Section: Figuresupporting
confidence: 64%
“…These subtle effects are presumably a consequence of exchange bias between the Dy 3+ centres affecting the rate of relaxation via QTM, suggesting that the borohydride ligands are effective at transmitting exchange interactions. 42 This proposal is consistent with a recent study of magnetic exchange in [Ln(BH 4 ) 3 ] (Ln = Gd–Tm), in which it was found that {HBH} bridges between the metal centres allow antiferro- or ferro-magnetic exchange, albeit with very small coupling constants. 43 …”
Section: Resultssupporting
confidence: 91%
“…Quantum tunneling of the magnetization is one of the key quantum signatures of the class of molecular nanomagnets commonly known as single-molecule magnets 1 . The phenomenon is observed in the bulk of polynuclear 3d metal clusters 2 , 3 and mononuclear 4 6 or multinuclear 7 9 lanthanide complexes, but can also be observed for single molecules deposited on inorganic surfaces 10 or incorporated into nanodevices 11 . Indeed, the quantum nature of these molecular objects renders them promising building units for molecular spintronics 12 , 13 , quantum computing 14 , 15 , and high-density information storage 12 , 16 .…”
Section: Introductionmentioning
confidence: 95%